From Customer Experience to Word-of-Mouth: The Mediating Role of Customer Satisfaction among Shopee Live Users in Indonesia - Gusnawati Gusnawati; Grace Indri; Nanda Dian Eka; Hairul Anam (Journal of Marketing Management and Innovative Business Review, 2026)
The rapid growth of live-commerce platforms has reshaped online shopping by offering interactive and engaging customer experiences. This study examines the effect of customer experience on word-of-mouth behavior, with customer satisfaction acting as a mediating variable among Shopee Live users in Indonesia. Grounded in Expectancy-Disconfirmation Theory (EDT), this research employs a quantitative approach using survey data collected from 120 Shopee Live users who had made at least one purchase through the platform within the previous six months. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that customer experience has a positive and significant effect on customer satisfaction, while customer satisfaction positively and significantly influences word-of-mouth behavior. However, customer experience does not directly affect word-of-mouth. Further analysis reveals that customer satisfaction fully mediates the relationship between customer experience and word-of-mouth. These findings suggest that positive customer experiences alone are insufficient to encourage recommendation behavior unless they first generate customer satisfaction. This study contributes to the live-commerce literature by highlighting the critical role of customer satisfaction as the mechanism through which customer experience translates into customer advocacy. The findings also offer practical insights for enhancing customer satisfaction and fostering positive word-of-mouth in live-commerce environments.